Operations Research - Bhatnagar, Mansi (Toronto Academic Press, 2024)
Operations Research is a field that applies advanced analytical methods to help make better decisions. This book provides a comprehensive introduction to the subject, covering topics such as optimization, modeling, simulation, and decision analysis. The book also includes real-world examples and case studies to illustrate how operations research can be applied to solve complex problems in various industries. Whether you're a student or a professional, this book is an essential resource for anyone interested in operations research and its practical applications.